ANALISIS PENGARUH CASH POSITION, DEBT TO EQUITY RATIO, DAN RETURN ON ASSETS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Gustian, Hedi; Bidayati, Utik (Jurnal Fokus Manajemen Bisnis, 2011)
This study is performed to examine the effect of Cash Position, Debt to Equity Ratio (DER), Return on Assets (ROA), and toward Dividend Payout Ratio (DPR) in companies that is listed in Indonesian Stock Exchange over period 2006-2008.The population of this research is 387 company that listed in Indonesian Stock Exchange period 2006-2008. Sampling technique used here is purposive sampling on criterion (1) the company that represent their financial report per 2006-2008, and (2) the company that continually share their dividend period 2006-2008. The data is obtained based on Indonesian Capital Market Directory (ICMD 2009) publication. It is gained sample amount of 12 companies. The analysis technique used here is multiple regression with the least square difference and hypothesis test using t-statistic to examine partial regression coefficient and F-statistic to examine the mean of mutual effect with level of significance 5%.This research results that Cash Position, Debt to Equity Ratio, and (DER) Return on Asset (ROA) gives are not significantly positive effect on dividend payout ratio (DPR). We suggest for investors in Indonesian Stock Exchange whose purpose to gain dividend should be pay attention for informations that issued by the company, because with those information they can make the best decision for their investments. On this research, Return On Asset (ROA) shows the most influencing variable toward DPR that pointed by the amount of beta standardized coefficients value 1,130, DER are 0,096, and Cash Position are 0.030